2022
DOI: 10.1038/s12276-022-00856-3
|View full text |Cite
|
Sign up to set email alerts
|

Targeted inhibition of tumor-derived exosomes as a novel therapeutic option for cancer

Abstract: Mounting evidence indicates that tumor-derived exosomes (TDEs) play critical roles in tumor development and progression by regulating components in the tumor microenvironment (TME) in an autocrine or paracrine manner. Moreover, due to their delivery of critical molecules that react to chemotherapy and immunotherapy, TDEs also contribute to tumor drug resistance and impede the effective response of antitumor immunotherapy, thereby leading to poor clinical outcomes. There is a pressing need for the inhibition or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(17 citation statements)
references
References 133 publications
1
16
0
Order By: Relevance
“…These results suggested that cellular MYC can regulates keystones of the tumor environment by potentially shifting exosomal content in breast cancer. Consistent with our findings, Kilinc et al reported that oncogene MYC alters RNA and protein composition of small extracellular vesicles secreted from cells (Kilinc et al, 2021; Li et al, 2022). Exosomes are increasingly challenging as important mediators of intercellular communication that play roles in the different steps of cancer.…”
Section: Discussionsupporting
confidence: 92%
“…These results suggested that cellular MYC can regulates keystones of the tumor environment by potentially shifting exosomal content in breast cancer. Consistent with our findings, Kilinc et al reported that oncogene MYC alters RNA and protein composition of small extracellular vesicles secreted from cells (Kilinc et al, 2021; Li et al, 2022). Exosomes are increasingly challenging as important mediators of intercellular communication that play roles in the different steps of cancer.…”
Section: Discussionsupporting
confidence: 92%
“…For example, exosomes secreted by APCs can stimulate the proliferation of T cells 42 . Exosomes derived from M2 macrophages can transfer key enzymes of the PG pathway to tumor cells, such as cyclo-oxygenase 1 (COX1) and TXA synthase 1 43 . Therefore, exosomes have great potential in tumor therapy including immunotherapy.…”
Section: Specific Functions Of Lipids In Tumor Cellsmentioning
confidence: 99%
“…Therefore, disruption and inhibition of the tumor inflammatory microenvironment as well as deeper tumor penetration seem to be promising strategies to eradicate the entire solid tumor for suppressing metastasis. 3 In the present study, the CDDP cross-linked HA in the outer layer not only is for the targeted co-delivery of CDDP and Hes entrapped liposomes but also exhibits anti-inflammatory effects. Liposome with a tunable size and versatile modification surface is widely used as a carrier of anti-cancer drugs, which can enhance penetration and accumulation of traditional chemotherapeutic drugs at tumor sites through the enhanced permeability and retention (EPR) effect and active targeting.…”
Section: ■ Discussionmentioning
confidence: 78%
“…Canonically, the tumor inflammatory microenvironment may contribute to a heterogeneous circumstance, which make chemotherapeutic drugs only to kill cancer cells at or near the periphery but not reach the interior area of the solid tumor, and to some extent, it can be used to explain the drug sensitivity decrease in CDDP treatment. Therefore, disruption and inhibition of the tumor inflammatory microenvironment as well as deeper tumor penetration seem to be promising strategies to eradicate the entire solid tumor for suppressing metastasis …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation